Diversity of Natural Product Biosynthetic Genes in the Microbiome of the Deep Sea Sponges Inflatella pellicula, Poecillastra compressa, and Stelletta normani - Borchert, E.; Jackson, S.; O'Gara, Fergal; Dobson, A. (Frontiers Research Foundation, 2016)
Three different deep sea sponge species, Inflatella pellicula, Poecillastra compressa, and Stelletta normani comprising seven individual samples, retrieved from depths of 760–2900 m below sea level, were investigated using 454 pyrosequencing for their secondary metabolomic potential targeting adenylation domain and ketosynthase domain sequences. The data obtained suggest a diverse microbial origin of nonribosomal peptide synthetases and polyketide synthase fragments that in part correlates with their respective microbial community structures that were previously described and reveals an untapped source of potential novelty. The sequences, especially the ketosynthase fragments, display extensive clade formations which are clearly distinct from sequences hosted in public databases, therefore highlighting the potential of the microbiome of these deep sea sponges to produce potentially novel small-molecule chemistry. Furthermore, sequence similarities to gene clusters known to be involved in the production of many classes of antibiotics and toxins including lipopeptides, glycopeptides, macrolides, and hepatotoxins were also identified.